Tinjauan akad murabahah li al-amr bi ashira - Hosen, Muhammad Nadratuzzaman (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2012)
This article aim to examine the term of mura>bah}a li al-a>mr bi ashira> (MLAB) is not widely known by practitioners and observers of Islamic economics. MLAB is a term of contemporary fikih that is different from classical mura>bah}a, the difference is not located at the level of the concept, but lies in the procedures performed. The most fundamental difference between mura>bah}a and MLAB is located on the parties to a contract; in MLAB parties directly involved are the sellers, banks and customers as a buyer, while the mura>bah}a parties involved only the seller and buyer. In addition, there is necessity in carrying out the promise of MLAB (waâad al-mulzim) the sale and purchase of a promise by the bank and the customer. The method of this article is to review the opinion of Islamic scholars in many books and articles, meanwhile the aim of this article is to explain the controversial behind of two contracts such as mura>bah}a, and mura>bah}a li al-a>mr bi ashira>>> in the implementation of Islamic Finance and Islamic Banks.